The analysis of sensitivity magnitude of a seismic complex established on Vernadsky station for seismic events from Sandwich islands area - V. M. Vaschenko; Yu.O. Gordienko; V.M. Shapka; V. M. Kaplaushenko; O.I. Liashchuk (Ukrainian Antarctic Journal, 2006)
The results of the analysis of sensitivity magnitude of a seismic complex established at Verrnadsky station are considered. The concept of a threshold magnitude, as a rating of an opportunity of revealing of seismic events from concrete region is entered. The results of the analysis of sensitivity magnitude for Sandwich Islands area are given.